2017
DOI: 10.3382/ps/pew495
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation of organic or inorganic manganese on eggshell quality, ultrastructure, and components in laying hens

Abstract: This study evaluated the effects of dietary supplemental levels and sources of manganese (Mn) on performance, eggshell quality, ultrastructure, and components in laying hens. A total of 1,080 46-wk-old Jing Brown hens were fed a basal diet (Mn, 32.7 mg/kg) for 2 wks laying and then randomly allocated to 9 groups that were fed a basal diet (control) or the basal diet supplemented with inorganic (MnSO4·H2O) or organic (amino-acid-Mn, 8.78%) Mn at 40, 80, 120, or 160 mg per kg of feed for 8 wks. Each group had 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 34 publications
2
24
1
Order By: Relevance
“…This study indicates that dietary Fe, Cu, Mn, and Zn supplementation levels and sources do not affect ADFI, egg Haugh unit, yolk color, or eggshell thickness, which is consistent with previous studies [17,18]. Tabatabaie et al [19] found that compared to a Zn un-supplemented group, supplemental organic zinc as Albino-Zn at 25 or 50 mg/kg decreased feed intake, and increased albumen height and Haugh unit, but ZnSO 4 in the same levels had minimal impact.…”
Section: Discussionsupporting
confidence: 93%
“…This study indicates that dietary Fe, Cu, Mn, and Zn supplementation levels and sources do not affect ADFI, egg Haugh unit, yolk color, or eggshell thickness, which is consistent with previous studies [17,18]. Tabatabaie et al [19] found that compared to a Zn un-supplemented group, supplemental organic zinc as Albino-Zn at 25 or 50 mg/kg decreased feed intake, and increased albumen height and Haugh unit, but ZnSO 4 in the same levels had minimal impact.…”
Section: Discussionsupporting
confidence: 93%
“…The ultrastructure of eggshell consists of 5 layers, including the shell membranes ( SM ), the mammillary knob layer ( ML ), the palisade layer, the vertical crystal layer, and the cuticle ( Arias et al,1993 ; Nys et al,1999 ; Gautron et al, 2021 ). It was reported that the average size, shape, and orientation of calcite crystals in the mammillary and palisade layers contribute to quality the eggshells ( Ahmed et al, 2005 ; Fathi et al, 2007 ; Dunn et al, 2012 ; Zhang et al, 2017a , 2017b ). So, it is necessary to study the influence of nutrition strategy on the ultrastructure of eggshell.…”
Section: Introductionmentioning
confidence: 99%
“…Differential contents of methionine in these groups were caused by the addition of Zn-Met in the premix, which was corrected by the addition of extra methionine (DL-methionine) in the premix. Hence all nutrients were kept at the same levels except for Zn content which met the nutritional requirements in the basal diet, which was in accordance with NY/T experimental periods for egg quality determination as reported previously (8) . Twelve hens from each treatment group (two hens per replication) were randomly selected and marked.…”
Section: Sample Collectionmentioning
confidence: 91%
“…To improve eggshell quality, great efforts have been taken in the genetics, environment and nutrition, especially in the micromineral nutrition (5)(6)(7)(8) . Zn, for example, is an essential metal micronutrient with particular physiological functions in all animals (9) .…”
mentioning
confidence: 99%